Gambaran perilaku dalam pemeliharaan gigi tiruan cekat (Kajian Pada RSGM-P FKG Universitas Trisakti) - Nathasya Trinity Milano; Eka Seftiana Indah Sari (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Tooth loss can lead to a decrease in a person’s quality of life. Fixed dentures are an option to replace missing teeth. Fixed denture maintenance is necessary to prevent unwanted complications such as inflammation of the gingiva and periodontal disease. Objectives: Knowing the behavior of patients in maintaining their fixed dentures at RSGM-P FKG Trisakti University. This research is a descriptive observational study with a retrospective cross-sectional method to describe the behavior of patients in maintaining their fixed dentures. Methods: A total 30 respondents that are using fixed dentures at RSGM-P FKG Trisakti University willing to participate. Results: Based on the research that has been done, it was found that woman patients had a higher average maintenance score compared to man. The younger the respondent's age, the better in maintaining their fixed dentures, then the scores varied for the level of education..Conclusion: Most patients who use fixed dentures at RSGM-P FKG Trisakti University have good maintenance.